Lactate Induces the Expressions of MCT1 and HCAR1 to Promote Tumor Growth and Progression in Glioblastoma - Longhitano, Lucia; Vicario, Nunzio; Tibullo, Daniele; Giallongo, Cesarina; Broggi, Giuseppe; Caltabiano, Rosario; Barbagallo, Giuseppe Maria Vincenzo; Altieri, Roberto; Baghini, Marta; Di Rosa, Michelino; Parenti, Rosalba; Giordano, Antonio; et al. (Frontiers in Oncology, 2022)
The tumor microenvironment (TME) plays a pivotal role in establishing malignancy, and it is associated with high glycolytic metabolism and lactate release through monocarboxylate transporters (MCTs). Several lines of evidence suggest that lactate also serves as a signaling molecule through its receptor hydroxycarboxylic acid receptor 1 (HCAR1/GPR81), thus functioning as a paracrine and autocrine signaling molecule. The aim of the present study was to investigate the role of lactate in glioblastoma (GBM) progression and metabolic reprogramming in an in vitro and in vivo model. The cell proliferation, migration, and clonogenicity were tested in vitro in three different human GBM cell lines. The expressions of MCT1, MCT4, and HCAR1 were evaluated both in vitro and in a zebrafish GBM model. The results were further validated in patient-derived GBM biopsies. Our results showed that lactate significantly increased the cell proliferation, migration, and colony formation capacity of GBM cells, both in vitro and in vivo. We also showed that lactate increased the expressions of MCT1 and HCAR1. Moreover, lactate modulated the epithelial–mesenchymal transition protein markers E-cadherin and β-catenin. Interestingly, lactate induced mitochondrial mass and the OXPHOS gene, suggesting improved mitochondrial fitness. Similar effects were observed after treatment with 3,5-dihydroxybenzoic acid, a known agonist of HCAR1. Consistently, the GBM zebrafish model exhibited an altered metabolism and increased expressions of MCT1 and HCAR1, leading to high levels of extracellular lactate and, thus, supporting tumor cell proliferation. Our data from human GBM biopsies also showed that, in high proliferative GBM biopsies, Ki67-positive cells expressed significantly higher levels of MCT1 compared to low proliferative GBM cells. In conclusion, our data suggest that lactate and its transporter and receptor play a major role in GBM proliferation and migration, thus representing a potential target for new therapeutic strategies to counteract tumor progression and recurrence.